Are renewable energy subsidies effective? Evidence from Europe. (July 2017) - Nicolini, Marcella; Tavoni, Massimo
Abstract: We test if policy support for renewable electricity have been effective in promoting renewables in the five largest European countries in the period 2000–2010. We collect data on the exact amount of monetary incentives and the average tariffs granted. The econometric analysis reveals a positive correlation between subsidies and the production of incentivized energy, as well as the installed capacity. We find that a 1% (1c€) increase in the incentive (tariff) leads to an increase in renewable generation of 0.4–1% (18–26%). Feed-in tariffs appear to outperform tradable green certificates. Overall, the analysis shows that these policies have been effective in promoting renewable energy, both in the short and in the long run.